PROPERTIES OF COMPOSITE GYPSUM BINDERS WITH BINARY FILLER AND SUPERPLASTICIZER C-3 - Ruzmetov Fazliddin Sharifboevich; Amirov Temirbek Tursoat ugli; Toshev Nodir Komil ugli (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
The article presents the results of studies on the influence of superplasticizing C-3 additives on the properties of composite gypsum binders with binary fillers of natural origin, consisting of basalt and limestone fillers. It has been established that a mixture of mineral additives and superplasticizer C-3 helps to increase the degree of filling of the binder without reducing the strength of gypsum stone from 12 to 15% when basalt and limestone are used as fillers, from 13 to 21 and from 10 to 25% when introducing basalt filler together with the original or washed quartz sand, respectively.